Evaluation of the efficacy of humic acids to counteract the toxic effects of aflatoxin B1 in turkey poults - Maguey-González, Jesús Adonai; Nava-Ramírez, María de Jesús; Gómez-Rosales, Sergio; Ángeles, María de Lourdes; Solís-Cruz, Bruno; Hernández-Patlán, Daniel; Merino-Guzmán, Rubén; Hernandez-Velasco, Xochitl; Hernández-Ramírez, Juan Omar; Loeza, Ileana; Senas-Cuesta, Roberto; Latorre, Juan D.; et al. (Frontiers in Veterinary Science, 2023)
This study aims to evaluate the efficacy of humic acid (HA) from worm-compost as an adsorbent for aflatoxin B 1 (AFB 1 ) in turkey poults. The experiment involved the inclusion of 0.25% (w/w) HA in This is a provisional file, not the final typeset article the diet of turkey poults consuming an aflatoxin-contaminated feed (250 ng AFB 1 /g). A total of 350 1-day-old female Nicholas-700 turkey poults were randomly allocated to five equal groups: Negative control (basal diet); Positive control (basal diet + 250 ng AFB 1 /g; HA (basal diet + 0.25% HA); HA + AFB 1 (basal diet + HA + 250 ng AFB 1 /g); and Zeolite + AFB 1 (basal diet + 0.25% Zeolite + 250 ng AFB 1 /g). Each group had seven replicates of 10 poults (n= 70). The impact of HA addition was evaluated in terms of performance parameters, relative organ weights, liver histological lesions, as well as serum biochemical and hematological constituents. In general, the addition of HA improved the body weight (BW), body weight gain (BWG) and feed conversation rate (FCR). Furthermore, HA effectively mitigated the toxic effects caused by the AFB 1 in the majority of the analyzed variables. The results indicated that HA effectively counteracted the AFB 1 -induced toxic effects in turkey poults. Based on these findings, it can be concluded that HA are capable of removing AFB 1 from the contaminated diet.